The rise of the randomistas: on the experimental turn in international aid - and Donovan, Kevin P. (Economy and Society, 2018)
In recent years, the use of experimental methodologies has emerged as a central means of evaluating international aid interventions. Today, proponents of randomized control trials (so-called randomistas) are among the most influential of development experts. This paper examines the growth of this thought collective, analysing how uncertainty has become a central concern of development institutions. It demonstrates that transformations within the aid industry – including the influence of evidence-based policy, the economization of development and the retreat from macro-planning – created the conditions of possibility for experimentation. Within this field, the randomistas adeptly pursued a variety of rhetorical, affective, methodological and organizational strategies that emphasized the lack of credible knowledge within aid and the ability of experiments to rectify the situation. Importantly, they have insisted on the moral worth of experimentation; indeed, the experimental ethic has been proposed as the way to change the spirit of development. Through causal certitude, they propose to reduce human suffering. The rise of experimentation has not, however, eliminated accusations of uncertainty; rather, it has redistributed the means through which knowledge about development is considered credible.
Keywords: Development; Evidence; Experimentation; aid; uncertainty